2015
DOI: 10.3928/00904481-20150812-11
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Con Debate: Protracted Bacterial Bronchitis as a Cause of Chronic Cough in Children

Abstract: Pro: Children with chronic cough present a diagnostic challenge. Protracted bacterial bronchitis (PBB) is a chronic, persistent bacterial infection of conducting airways defined by the presence of cough for longer than 4 weeks that resolves with antimicrobial therapy and without an alternative diagnosis. The diagnosis is made by the findings of increased bronchial secretions and edema of the lower airways on flexible bronchoscopy and positive cultures on bronchoalveolar lavage. It is speculated that an initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 35 publications
1
13
0
1
Order By: Relevance
“…PBB with chronic cough and wheezing was likely to misdiagnosis as asthma [13]. These children can be distinguished from asthma which was characterized by a dry cough and effective corticosteroid treatment [4,27]. However, some children with unsatisfactory effects after antibiotic therapy should pay attention to the diagnosis of asthma because some PBB were finally diagnosed as asthma.…”
Section: Discussionmentioning
confidence: 99%
“…PBB with chronic cough and wheezing was likely to misdiagnosis as asthma [13]. These children can be distinguished from asthma which was characterized by a dry cough and effective corticosteroid treatment [4,27]. However, some children with unsatisfactory effects after antibiotic therapy should pay attention to the diagnosis of asthma because some PBB were finally diagnosed as asthma.…”
Section: Discussionmentioning
confidence: 99%
“…If PBB fails to respond or becomes recurrent, further investigations such as complete blood count, assessment of immunoglobulins, functional antibody response to vaccination, sweat test, and high-resolution CT are required to rule out other etiologies such as cystic fibrosis, primary ciliary dyskinesia, immunodeficiencies, or dysfunctional swallowing and aspiration issues. [ 40 ] CT scan has an important role, because it has been demonstrated that children with a chronic wet cough failing to resolve after 4 weeks of appropriate oral antibiotics have increased likelihood of developing bronchiectasis. [ 41 ]…”
Section: Therapymentioning
confidence: 99%
“…Nekateri strokovnjaki pa opozarjajo, da so diagnostična merila za PBB preveč nespecifična in lahko pripeljejo do prepogoste postavitve diagnoze in zato nepotrebnega dolgotrajnega predpisovanja antibiotikov. To lahko privede do razvoja odpornih sevov (19).…”
Section: Značilnosti Kašlja Možno Obolenjeunclassified